Remote control of hydrostatic drive mechanisms for hoisting machinery and logistics centers - Grigorov, Otto; Stryzhak, Vsevolod; Ziubanova, Daria (University "Politehnica" of Bucharest, 2015)
The analysis of the crane or loader travel mechanism construction with hydrostatic drive and low-moment hydraulic motor has been performed. It has been proposed that the electric circuit of pump performance remote control system that meets the requirements applicable to the crane drives control system. The zero-setter design has been developed for hydraulic drive emergency braking in case of an emergency, while the bridge runover on the obstacle when travel limit switches of the traveling mechanism triggered , and also the electric drive motor of the pump and electric control scheme of pump productivity loses power. The hydraulic circuit of the lifting machines mechanism is presented and its operating principle is described. Implementation and testing of remote control system elements are implemented on the travel mechanism experimental stand of the crane with a lifting capacity of 32/5 t that is described in the article.The stand design allows to provide long-term trials in a wide range of static and dynamic loads, to realize implement typical operation cycles and to record the nature of dynamic loads and energy consumption. In consequence of the research it was proved that hydrostatic drive with low-moment hydraulic drive and described remote control system has deep adjustable speed for a given program, softens dynamic load transients, and saves a significant amount of power during acceleration and braking.
Keywords: hydrostatic drive; travel mechanism; control system; low-moment hydraulic motor; hydraulic motor; servomotor